Viral vector malaria vaccines induce high-level T cell and antibody responses in West African children and infants - Bliss, C; Drammeh, A; Bowyer, G; Edwards, N; Hill, A; Hodgson, S; Roberts, R; Duncan, C; Lawrie, A; Imoukhuede, E; Ewer, K (Nature Publishing Group, 2016)
Heterologous prime-boosting with viral vectors encoding the pre-erythrocytic antigen ME-TRAP induces CD8+ T cell-mediated immunity to malaria sporozoite challenge in European malaria-naïve and Kenyan semi-immune adults. This approach has yet to be evaluated in children and infants. We assessed this vaccine strategy among 138 Gambian and Burkinabe children in four cohorts: two to six-year olds in The Gambia; five to 17 month olds in Burkina Faso; five to 12 month olds and ten week olds in The Gambia. We assessed induction of cellular immunity, taking into account the distinctive haematological status of young infants, and characterised the antibody response to vaccination. T cell responses peaked seven days after boosting with MVA, with highest responses in infants aged ten weeks at priming. Incorporating lymphocyte count into the calculation of T cell responses facilitated a more physiologically relevant comparison of cellular immunity across different age groups. Both CD8+ and CD4+ T cells secreted cytokines. Induced antibodies were up to 20-fold higher in all groups compared with Gambian and UK adults, with comparable or higher avidity. This immunisation regimen elicited strong immune responses, particularly in young infants, supporting future evaluation of efficacy in this key target age group for a malaria vaccine.